24 Hour Ambulatory Blood Pressure Monitoring In Patients With Chronic Kidney Disease (Indian Journal of Applied-Basic Medical Sciences, 2022)
Background and aims: Chronic Kidney Disease (CKD) And Hypertension(HTN) Are  Associated With Each Other Invariably And Each Can Cause Or Aggravate The  Other.Hypertension Is A Strong Independent Risk Factor For ESRD And Contributes To The  Disease Itself, Or Most Commonly, To Its Progression.24 Hour Ambulatory Blood Pressure  Monitoring (ABPM) Is Superior To Clinic BP Monitoring In Predicting The Risk In  Hypertensive CKD Patients The Aim Of This Study Was To Review The Results Of  ABPM In CKD Patients Which Can Guide In Changing The Antihypertensive Therapy . Material and Methods: This Prospective Observational Study Having 63 Patients. All The Patients Fulfilling The Criteria Of CKD According To The KDIGO Guidelines And Above  18 Years Of Age Were Included In This Study Whose 24 Hour Ambulatory Blood  Pressure Was Measured.Detailed History, Clinical Examination And Relevant  Investigations Were Recorded Comparisons Of Various ABPM Characteristics WERE  Done And P Value
Keywords: Chronic Kidney Disease; Hypertension Dialysis; Ambulatory Blood Pressure; Diurnal Variation